Menggagas Transparansi Operasional BPRS Perspektif Digital - Tarmizi, Achmad Chumaidi (FALAH Jurnal Ekonomi Syariah, 2016)
Syariah financing people bank so called as BPRS, give warranty to the borowers , that every operations free of elements gambling (maysir), uncertainty (gharar), and interest (riba). Warranty with a certain step to give an explanation and information of all the aspect of operational done by BPRS can be called as the transparency. Thus, improving the transparency in BPRS need to optimized. Transparency which includes a whole operational activities with the stakeholders need to be enhanced, because the lack of transparency could caused to uncertainty (gharar) that impact to the faith of stakeholders. This study aimed to explore in depth views relating to two things; first, the development of transparency on BPRS; especially in operational activities businesses and correlation with the stakeholders. Second, the role of information technology in the process of transparency, and its impact on BPRS or the National Economy.